The Potential of Bait al-M l wa Tamwil (BMT) in Developing The Border Area of Indonesia - Malaysia - Muhammad Iqbal Maulana; Nashr Akbar (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2019)
Indonesia border area (West Kalimantan, Sambas) - Malaysia (Sarawak) is a potential area. Strategic location and direct borders with other countries such as Malaysia make this area easy to interact economically with neighboring countries, either in the form of Asean Economic Community (MEA) or Brunei Indonesia Malaysia Philippines - East Asian Growth Area (BIMP - EAGA). But the reality is there are still socio-political and economic disparities. An unanticipated social and economic gap will interfere and affect the pattern of national development strategies, and affect national interests. Therefore, the border area of Indonesia (West Kalimantan, Sambas) - Malaysia (Sarawak) should be built and developed in order to eliminate the gaps that occur. This research tries to know the potential of Baitul Mal wa Tamwil (BMT) in developing border area of Indonesia - Malaysia by prioritizing welfare approach. The decision framework is structured using the ANP approach of the Benefit Opportunity Cost Risk (BOCR) network. All BOCR elements are reviewed from a community perspective and obtained through in-depth interviews with experts (academics), regulators, and practitioners. The results of this study conclude that the benefits and opportunities aspects have significantly more weight than the load and risk aspects. Alternative strategies are also proposed in this study to maximize benefits and opportunities and minimize costs and risks. An alternative strategy considered to be the first priority to be implemented according to respondents is the capital of third parties.Keywords: ANP-BOCR, BMT, Border Area